Fintech in COVID-19 and beyond: What factors are affecting customers' choice of FinTech applications? - Mohammad K. Al-Nawayseh (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Accessing financial services is considered one of the main challenges facing communities during crises. This research studies the role of using FinTech applications to build resilience during the COVID-19 pandemic. The research empirically examines the factors affecting Jordanian citizens' intention to use FinTech applications. The sample of the research comprised 500 potential FinTech service users in Jordan. Based on the research conceptual model, five hypotheses were developed and tested using structural equation modeling techniques (SEM-PLS). The research results indicate that perceived benefits and social norms significantly affect the intention to use FinTech applications. However, it has been found that perceived technology risks do not significantly affect the intention to use FinTech applications. Moreover, the results also indicate that customer trust is significantly mediating the relationship between perceived risks and intention to use FinTech applications. FinTech service providers should insure that their products are easy to use, fulfill needs and protect consumers' data in order to ensure trust, hence positively influencing consumer adoption.
Keywords: 650; open innovation; COVID-19; FinTech; Jordan; resilience